Is mating in the Túngara Frog (Engystomops pustulosus: Leptodactylidae) random or non-random? - Barquero Arroyo, Marco David (2017)
Random and non-random mating result from sexual selection, and both can occur across populations of the same species. Body size is a trait commonly used to determine if mating is random or non-random, and for the latter there are two possible outcomes: size-assortative mating and size-dependent mating. Females of the Túngara Frog (Engystomops putulosus) from Panama are larger than males, although no correlation in the body size of amplectant individuals has been reported, which suggests random mating. Here, we evaluate whether random or non-random mating (i.e. size-assortative or size-dependent mating) occurs in a population of E. pustulosus from southwestern Costa Rica. We measured the body size of amplectant individuals in the field, and did not find a significant difference between the snout–vent length (SVL) of paired males and females or a correlation among the SVLs of all paired individuals. When we considered body size differences among paired males and females, however, we observed size-dependent mating. We suggest that non-random mating must be determined by using more robust analyses, and that a comparison of life-history traits and mating strategies among populations is necessary to determine divergence.